Advances in autoimmune myasthenia gravis management. (3rd July 2018) - Wang, Shuhui; Breskovska, Iva; Gandhy, Shreya; Punga, Anna Rostedt; Guptill, Jeffery T.; Kaminski, Henry J.
ABSTRACT: Introduction: Myasthenia gravis (MG) is an autoimmune neuromuscular disorder with no cure and conventional treatments limited by significant adverse effects and variable benefit. In the last decade, therapeutic development has expanded based on improved understanding of autoimmunity and financial incentives for drug development in rare disease. Clinical subtypes exist based on age, gender, thymic pathology, autoantibody profile, and other poorly defined factors, such as genetics, complicate development of specific therapies. Areas covered: Clinical presentation and pathology vary considerably among patients with some having weakness limited to the ocular muscles and others having profound generalized weakness leading to respiratory insufficiency. MG is an antibody-mediated disorder dependent on autoreactive B cells which require T-cell support. Treatments focus on elimination of circulating autoantibodies or inhibition of effector mechanisms by a broad spectrum of approaches from plasmapheresis to B-cell elimination to complement inhibition. Expert commentary: Standard therapies and those under development are disease modifying and not curative. As a rare disease, clinical trials are challenged in patient recruitment. The great interest in development of treatments specific for MG is welcome, but decisions will need to be made to focus on those that offer significant benefits to patients.